The Mathematical Instructional Model in Fostering Critical Thinking - Buhaerah; Siri Dangnga (Journal of Research on Mathematics Instruction (JRMI), 2020)
The main issues raised in this research was” how the process and results of the development of mathematical learning model that develops critical thinking skills in brief development mathematical instruction model in fostering critical thinking, colled MICT. The model developed new MICT until the test phase was limited, therefore to determine its effectiveness on a broader scope. Aspects of students' critical thinking applied in this model can be modified by teachers who are interested in implementing this model, modification can be done by adjusting the environment and culture of the students.